Substitution method:
6x+5y=17
x=53-8y
Solve for a variable and substitute it in to one of the equations. The easiest way with these two equations is to take x from the second equation and substitute it in to the first equation.
6(53-8y)+5y = 17
618 - 48y + 5y = 17
-48y + 5y = 17 - 618
-43y = -601
y = -601/-43
Then you plug y in to one of the equations and solve for x.
x = 53 - 8*(601/43)
Elimination method: The idea is you multiply one equation by a constant so either x or y has the same coefficient as the x or y in the other equation.
Example:
#1) x + 3y = 4
#2) 5x + 2y = -19
We need to pick a variable to eliminate. The easiest way is to eliminate the x in the second equation. To do this we multiply the first equation by 5 and subtract it from the second.
5*(x+3y) = 5*4
5x+15y = 20
It's tricky to write out the next part online, you normally write the equations directly over each other with a subtraction sign.
5x + 2y - 5x - 15y = -19 - 20
-13y = -39
At this point you can easily solve for y.
y = -39/-13 = 3
Then substitute y=3 in to one of the first equations.
x + 3y = 4
x + 3*3 = 4
x + 9 = 4
x = 4 -9
x = -5
--The problem you gave is slightly different.
2x+3y=5
4x+6y=10
In this problem you'd multiply the first equation by 2 and subtract it from the second. The new second equation is then 0 = 0.
This set of equations is not solvable. Using the elimination method one of the equations is completely eliminated because they are equivalent equations.
How do I solve these problems, I really need help.
Solve by substitution method
6x+5y=17
x=53-8y
Solve by elimination method
2x+3y=5
4x+6y=10
2 answers
how do you do this equation by using elimination.? 8x-5y=11
4x-3y=5
4x-3y=5